KEJADIAN ISPA PADA ANAK USIA KURANG DARI 12 TAHUN DI WILAYAH KERJA PUSKESMAS SEBENGKOK, KOTA TARAKAN - Musfirah, Musfirah; Kamisa, Rizki (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2023)
Acute Respiratory Infection (ARI) disease is the biggest health problem that occurs most often in Tarakan City,. This study aims to determine the relationship between parental knowledge about ARI, bedroom occupancy density and smoking activity in the home with the incidence of ARI in children aged less than 12 years in the working area of the Sebengkok Health Center, Tarakan City. This study used a cross sectional design with a sample of 61 respondents selected based on the Simple Random Sampling technique. Methods of data collection using questionnaires and measurement sheets. The results of the analysis using the Fisher's exact test showed that there was no relationship between parental knowledge and the incidence of ARI (p-value = 0.279) and the analysis used the chi-square test, namely that there was no relationship between bedroom occupancy density (p- value = 0.613) and no the relationship between smoking activity in the home (p-value = 0.591) and the incidence of ARI in children aged less than 12 years old in the work area of the Sebengkok Health Center, Tarakan City